THE COMPARATIVE EFFICACY OF AEROSOL NITROGLYCERIN FORMS IN RAPID RELIEF OF ANGINA PECTORIS - A. I. Scherbak (Российский кардиологический журнал)
The comparative efficacy of aerosol nitroglycerin forms in rapid relief of angina pectoris.